Gender Equality in Education: Challenges and Solutions in The Age of Modernization - A. Erni Ratna Dewi; Mulyadi Mulyadi; Erwin Nurdiansyah (Journal of Pedagogi, 2025)
Gender equality in education is a global issue that still faces major challenges, especially in developing countries. Gender stereotypes that limit women to domestic roles and traditional fields of study hinder their participation in sectors such as science and technology, exacerbating the gender gap in the world of work. In addition, unequal access to technology and online education is also a significant barrier, especially for women living in remote or low-income areas. However, technological advances and globalization offer opportunities to improve these conditions, through technology training and digital empowerment programs. To achieve this, inclusive education policies that are free of gender bias need to be implemented, in addition to the implementation of affirmative policies such as providing women-only scholarships and digital skills training. Utilizing education technology, such as online education, can expand access for women without location or time barriers. Through this approach, educational equality can be achieved, providing greater opportunities for women's economic empowerment and creating a more just and inclusive society. This study aims to examine the challenges and solutions to gender equality in education and identify the steps that need to be taken to achieve such equality.